Identification of fungi from Otomycosis patients in Duhok city and their in vitro antifungal susceptibility testing - Soleen A. Sultan; Asia A. M. Saadullah (Zanco Journal of Pure and Applied Sciences, 2023)
The aim of this study was to determine the most common causative agents of otomycosis in Duhok city, Iraq; and subsequently study their sensitivity to the most commonly prescribed Drugs. From August 2021 till October 2021, a total of 90 patients (46 females and 44 males) who attended the outpatient clinic of ear, nose and throat (ENT) department at Azadi teaching hospital; were clinically examined for mycotic otitis. Ear debris was collected by sterile swabs and transferred to the laboratory for direct microscopic and macroscopic examination by culturing on sabouraud dextrose agar, potato dextrose agar and CHROM Agar Candida. Antifungal drugs were dissolved with (dimethyl sulfoxide) DMSO and used for evaluation of antifungal sensitivity by agar well diffusion method against commonly used antifungal drugs namely; Fluconazole, Itraconazole, Terbinafine, Nystatin, Amphotericin B, and Clotrimazole. In this study positive fungal infections were found in 88 (97.8%) of the collected samples, and it was more common among patients that aged 40 to 49 years. Mycological examination revealed the isolation of 24 genera and species with one variety. The most common fungal isolates were Candida (88.9%), followed by Aspergillus (28.8%) and non-identified yeast (25%), Penicillium (8.9%). Among the identified species, Candida krusei (44.4%) and Candida albicans (16.7%) followed by Aspergillus niger (15.6%) were the predominant species isolates.